Non-timber forest products: local knowledge and use of edible wild fruit in Chocó, Colombia (UNED Research Journal, 2019)
Introduction: non-timber forest products provide food security in rural contexts. Objective: to expand the list of promising wild plants in Chocó, Colombia. Methods: we interviewed 150 adults (10% of the population) with published ethnobotanical formulas. Results: we recorded 21 species (13 botanical families, numerically dominated by Arecaceae with six). The community rated two species higher in the Index of Use Value: Oenocarpus bataua (26%) and Attalea allenii (12%). Women had the greater participation and contributed most of the information. Conclusion: the results described in this research serve as the basis for the construction of public policies that include strategies specific to the rural contexts of the region, which promote sustainable economic development at different scales, based on the responsible use of natural resources.
Keywords: local knowledge; wild; use value; gender